Transformasi Digital Sekolah Dasar dalam Meningkatkan Pelayanan kepada Murid dan Wali Murid SDN 2 Labuhan Lombok - Ida Royani; Drs. Amil; Muhammad Rahmatul Burhan (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
This study aims to analyze how digital transformation is implemented at SDN 2 Labuhan Lombok to improve services to students and parents, and to identify challenges encountered during the process. Digital transformation, in this context, encompasses changes to the learning system, administration, facilities, and technology-based counseling services. The study used a qualitative approach with data collection techniques including observation, in-depth interviews, and documentation. The results indicate that digital transformation has had a positive impact on communication effectiveness, administrative service efficiency, and parental involvement in the educational process. However, obstacles remain, such as limited infrastructure, low digital literacy, and minimal technology training for teachers and parents. With adequate infrastructure support and strengthening human resource capacity, digital transformation in elementary schools has the potential to sustainably improve the quality of educational services.